All the President's men [compact disc, unabridged] - Bernstein, Carl, 1944- (Recorded Books, 2004)
At first, it was a simple story. Democratic headquarters at the Watergate complex in Washington, D.C. had been burglarized. But as Washington Post reporters Bernstein and Woodward dug deeper, a trail of corruption wound its way back to President Richard Nixon. Before long, Nixon's reign was over.